Sexual Quality of Life in Inflammatory Bowel Disease: A Multicenter, National-Level Study. Issue 5 (27th August 2019) - Roseira, Joana; Magro, Fernando; Fernandes, Samuel; Simões, Carolina; Portela, Francisco; Vieira, Ana Isabel; Patita, Marta; Leal, Carina; Lago, Paula; Caldeira, Paulo; Gago, Tânia; Currais, Pedro; et al.
Abstract: Background: The impact of inflammatory bowel disease (IBD) on sexual health is a leading concern among patients. Most studies focus on sexual dysfunction rather than patient-perceived sexual quality of life (SQoL). We aimed to assess SQoL in IBD patients compared with healthy controls. Methods: This is a multicenter, cross-sectional study of IBD patients (n = 575 with Crohn's disease and n = 294 with ulcerative colitis), compared with healthy controls (n = 398), that used an anonymous self-administered questionnaire. This multimodal questionnaire included sociodemographic data and 4 validated instruments: Short IBD Questionnaire, Social Desirability Scale, Sexual QoL Questionnaire–Male/Female, Nine-item Patient Health Questionnaire. Results: Inflammatory bowel disease patients reported lower SQoL (men: 77.29 vs 83.83; P < 0.001; women: 70.40 vs 81.63; P < 0.001) compared with controls. Among IBD patients, SQoL was positively correlated with health-related quality of life (HRQoL) and negatively correlated with depression symptoms. Perianal disease was associated with lower HRQoL and higher incidence of depression, but only impacted SQoL in men. In linear regression analysis for men, SQoL was associated with age, marital status, and depression (β, –2.101; 95% confidence interval [CI], –2.505 to –1.696; P < 0.001). In women, SQoL was associated with depression (β, –1.973; 95% CI, –2.313 to –1.632; P < 0.001) only. Conclusions: Patients with IBD had impaired SQoL compared with healthy controls. Age, widow status, and depression were independent predictors of SQoL in men with IBD, whereas in women depression was the only independent predictor. Emotional and self-esteem issues were the main concerns reported by IBD patients regarding sexual health. Abstract : Most studies focus on sexual dysfunction rather than patient-perceived sexual quality of life (SQoL). Patients showed impaired SQoL compared with controls when using an instrument that evaluates the different aspects of sexual health. Most concerns in this context were related to emotional issues and self-esteem.